How human aspects impress Agile software development transition and adoption - Gandomani, Taghi Javdani; Zulzalil, Hazura; Abdul Ghani, Abdul Azim; Md Sultan, Abu Bakar; Yatim Sharif, Khaironi (Science and Engineering Research Support Society, 2014)
Many software companies are interested in using Agile methods in their software projects. Contrary to traditional software development methods, Agile methods are people oriented. This fact shows the significant role of individuals in these methods. Increasing prevalence of Agile methods forces software companies to consider people related factors as critical issues in adoption and transition to Agile methods and practices. This article focused on human aspects of Agile transformation process by conducting a Grounded Theory study involving 32 Agile experts. The main contribution of this article is identification and classification of diverse human aspects of Agile transformation process. Analyzing collected data showed that human aspects of Agile transformation process can be classified in several categories. While some of them are impediments to change, some others act as change accelerators. At the same time people’s perceptions about change process and incentive factors can shape and form human aspects during the Agile transformation process. Each of these categories encompasses its own factors which have negative or positive effect on change process.